Retention in Junior Giants, a sport-based youth development program: what factors are associated with intentions to return? - Bolter, Nicole D.; Kipp, Lindsay E.; Greenwood, P. Brian (Frontiers in Sports and Active Living, 2024)
While evaluation research shows that physical activity-based youth development (PA-PYD) programs can have a positive impact on social and emotional growth, less is known about which participants return year after year and what factors are associated with their continued participation. The Junior Giants is a sport-based youth development program for 5-18-year-old boys and girls that is non-competitive and free to participate. The 8-week program uses baseball and softball as platforms for teaching life skills and fostering social emotional competencies. This mixed-methods study evaluated quantitative factors associated with intentions to return to the program the following year and qualitative reasons why parents/caregivers intended not to re-enroll their child. Parents/caregivers of Junior Giants participants (N = 8,495) completed online surveys about their child’s demographics, social emotional climate and learning, character development, and intentions to return the following year. Chi-square and t-test analyses revealed significant differences (p < .001) between intended returners (n = 7179, 84.5%) and those who reported no/undecided on returning (n = 1316, 15.5%). Intended returners were significantly more likely to be identified as Latino and be in their second year of participation. Significant predictors of a binomial logistic regression [𝜒2 (df = 22) = 1463.25, p < .001] included age, race/ethnicity, years played, character development, reading, league experiences, physical activity, and perceived support, with small to medium effect sizes. Using responses from a subset of 217 parents/caregivers who reported their child would not return to the program, a thematic analysis resulted in seven themes: Lack of Organization and Communication; Dissatisfied with Coaching, Didn’t Learn Baseball/Softball, Not Competitive Enough, Skill Levels Not Matched, Aged Out, and Non-Program Related Reasons. Quantitative results contribute to the literature on predictors of retention in youth development programs, while qualitative findings echo common motives cited for dropout in youth sport. Both provide opportunities for reflection and potential changes to future programming.